Use of masks in public places in Poland during SARS-Cov-2 epidemic: a covert observational study - Maria Ganczak; Oskar Pasek; Łukasz Duda - Duma; Dawid Świstara; Marcin Korzeń (BMC, 2021)
Abstract Background Face masks have been employed in the COVID-19 pandemic plans as a public and personal health control measure against the spread of SARS-CoV-2. In Poland, obligatory wearing of masks in public spaces was introduced on April 10th, 2020; a relaxation of previous universal measures was announced on May 29th, 2020, limiting use to indoor public places. Objective To assess use of masks or other protective devices in public spaces in Poland during the SARS-Cov-2 epidemic. Methods A non-participatory covert observational study was conducted on three dates, (10.05/18.05/25.05.2020) at public spaces in 13 regions with different risks. Ten consecutive individuals were observed by each of 82 medical students (n = 2460 observations), using a structured checklist. Results Among 2353 observed persons, the female/male ratios were 1.0, 1.1, and 1.0 on the three dates. Almost three quarters - 73.6% (n = 552/750) were using masks on date 1, 66.5% (544/818) on date 2; and 65.7% (516/785) on date 3. Cloth masks predominated on all dates (64.7-62.3%-62.6%), followed by medical (23.4-28.5%-26.9%). Being female (OR = 1.77-1.47-1.53 respectively) and location in a closed space (OR = 2.60-2.59-2.32) were each associated with higher usage. Participants in sports were about two times less likely to use masks (OR = 0.64-0.53-0.53) as compared to other activities. The proportion using masks correctly decreased gradually over time (364/552; 65.9%; 339/544; 62.3% and 304/516; 58.9%). More females wore masks correctly (date 1: 205/294; 69.7% vs 159/258; 61.6%, and date 3: 186/284; 65.5% vs 118/232; 50.9%; p = 0.045; p = 0.0008 respectively). Uncovered noses (47.3-52.7%) and masks around the neck (39.2-42.6%) were the most frequent incorrect practices. Conclusions Practices were not in line with official recommendations, especially among males, and deteriorated over time. Cloth masks were predominantly used in public spaces. Health promotion, through utilizing all available communication channels, would be helpful to increase compliance.